Evaluation of the Online New Student Admission Program (PPDB) Islamic Education Institutions at Bengkulu City (Case Study of PPDB at MTs Negeri 1 Bengkulu City in 2022) - Hadi Winarto; Syukri Hamzah; Nadia Nur Ifani (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
The purpose of this study was to examine how the evaluation of online student admission program at one of Islamic education institute Bengkulu. The reaseach wes case study in MTsN 1 Bengkulu using CIPP evaluation model. This kind of evaluation is used in the research methodology. The data collection techniques used are interviews and documentation. The study's findings are as follows: 1) The context evaluation results assure that the admission of new students is impartial, open, responsible, nondiscriminatory, and fair 2). The committee's decision and the specifics of their responsibilities are the outcomes of the input evaluation, as are prospective students who register through the city PPDB website 3). Registration, choosing new students, announcements, and re-registration are all included in the assessment process. 4). The results of the product evaluation included 315 students who registered, which were accepted by 288 students.